‘Not the Same as Before’? Contested Discourses of Political Change in Thailand's 2023 Elections - Duncan McCargo (Journal of Current Southeast Asian Affairs)
The 2023 Thai general election was fought on the question of what it meant to be Thai: the progressives arguably won the argument, but the conservatives seized power anyway. The progressive Move Forward Party became the largest single party in the new parliament but was barred from forming a government. At the final election rally of his conservative United Thai Nation (UTN) Party on 12 May 2023, incumbent prime minister and former 2014 coup leader General Prayut Chan-ocha paused his speech to show a video ad critiquing a slogan popularized by Move Forward, which had pledged to ensure that Thailand would “not be the same as before.” The UTN ad parodied the slogan, depicting a Thai family in which young adults were at cross-purposes with their parents and grandparents, reflecting a collapse in traditions and standards of behaviour. UTN's negative campaigning epitomised a shift among Thai voters along the lines of two major cleavages: age (younger voters versus older ones) and ideology (progressive voters versus those supporting conservative values). This article uses the UTN video to explore how these cleavages were central to the 2023 Thai election campaign. The video was a seminal text for this election, offering an extraordinary insight into the mentality and moral posturing of the conservative side.